2019
DOI: 10.3390/cancers11111802
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNA: Dual Effects on Breast Cancer Metastasis and Clinical Applications

Abstract: As a highly heterogeneous malignancy, breast cancer (BC) has become the most significant threat to female health. Distant metastasis and therapy resistance of BC are responsible for most of the cases of mortality and recurrence. Distant metastasis relies on an array of processes, such as cell proliferation, epithelial-to-mesenchymal transition (EMT), mesenchymal-to-epithelial transition (MET), and angiogenesis. Long non-coding RNA (lncRNA) refers to a class of non-coding RNA with a length of over 200 nucleotid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 203 publications
(222 reference statements)
0
45
0
Order By: Relevance
“…Currently, a rising number of studies have managed to investigate the association between lncRNAs and breast cancer. LncRNAs have dual effects in BC metastasis by regulating invasion, migration, and distant metastasis of breast cancer cells [27]. In addition, lncRNAs have critical regulatory effects in the stemness and angiogenesis of breast cancer [28].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, a rising number of studies have managed to investigate the association between lncRNAs and breast cancer. LncRNAs have dual effects in BC metastasis by regulating invasion, migration, and distant metastasis of breast cancer cells [27]. In addition, lncRNAs have critical regulatory effects in the stemness and angiogenesis of breast cancer [28].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there is urgent need to exploit the novel and effective biomarkers for early diagnosis, treatment option, and survival evaluation to improve the prognosis for BRCA. In the past decades, more and more studies provided evidences to support that lncRNAs might play key roles in tumorigenesis, progression and invasion in breast cancer [15,35]. According to previous researches, lncRNAs were reported as crucial regulators in regulating cancer immunity [12].…”
Section: Discussionmentioning
confidence: 99%
“…Like miRNAs, there has been a multitude of studies linking the dysregulation of lncRNAs to cancer. Thus, it was repeatedly shown that abnormal expression of numerous lncRNAs among which, for example, MALAT1, HOTAIR, and DANCR, contributes to BC aggressiveness, metastasis formation, and hence BC patients' prognosis outcome 3 . Therefore, owing to their clinical implications and networks of crosstalk, both miRNAs and lncRNAs are explored as therapeutic and diagnostic options in cancer and subjected to extensive research.…”
Section: Non-coding Rnas In Cancermentioning
confidence: 99%